Microentrepreneurship and the business cycle: Is self-employment a desired outcome? - Federico S. Mandelman; Gabriel V. Montes Rojas (Federal Reserve Bank of Atlanta, 2007)
This paper links employment dynamics to the business cycle in order to examine the voluntary nature of self-employment in Argentina. Our results suggest that the transition to self-employment is more common during recessions and that the likelihood of becoming self-employed increases with the length of the recession and the unemployment duration. We find that the majority of self-employed workers do not have employees and earn significantly less than salaried workers. Individuals in this sector are often young and less educated and have trouble obtaining a salaried position regardless of the macroeconomic conditions. Middle-aged, college-educated individuals also tend to enter self-employment as a temporary refuge when they encounter difficulties during a recession. Our results suggest, however, that for entrepreneurs who have employees, entry into self-employment is procyclical and voluntary and has characteristics similar to those predicted for highly skilled risk-taking entrepreneurs. Including idiosyncratic entrepreneurial abilities in a standard job search model allows us to predict such labor market segmentation and the cyclical pattern of entrance into self-employment.
Keywords: J23; L25; E32; 330; microfirms; self-employment; business cycles